Interaksi Wilayah Kepulauan Spermonde Kota Makassar - Muh. Afdhal Fadhil; Ihsan Ihsan; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The coastal areas and small islands in the Makassar city have a variety of potential antraction and rich of biodiversity that have a very important socio-ecological roles and functions for the community and the environment. Supermonde islands of Makassar city have a lot of potential that must be based on the suitability and carrying capacity of the islands, the interaction of the Archipelago region is very important for increasing the potential of the Spermonde islands itself with the interaction or reciprocal relationship between Spermonde Islands and Makassar city so that economic turnover can also be occured. The objectives of this study include 1) Learn the potential that exists in the Spermonde Islands, and 2) analyze the interaction of the area on the Spermonde Islands. This study uses secondary data which is analyzed using GIS so that we can find out the potential location and regional interactions, for example the potential visit to the island, the education relationship of island residents to Makassar City and find out the economic potential of the islands. The results of this study indicate 1) what potentials does the islands have, 2) explaining the regional interactions, both visitors potential, island education relations to Makassar City and the economy so that the emergence of mutual relations between the Spermonde islands and Makassar City.